The Relationship Between Intellectual Capital, Human Capital, Public Relation Strategy, AI Integration, Corporate Social Responsibility, And Company Image - Mutiara Khikmatul Maolidah; Nuril Khusni Al Amin; Vallery Imanuel (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This research aims to investigate the interconnectedness among intellectual capital, human capital, public relation strategy, AI integration, corporate social responsibility (CSR), and company image within organizational settings.The study utilizes purposive sampling to select participants from diverse industries. Data collection involves in-depth interviews and document analysis. Through thematic analysis, the research explores the nuanced relationships among the variables, uncovering how they contribute to shaping company image. The findings shed light on the significance of strategic integration of intellectual and human capital, effective public relation strategies, AI utilization, and CSR initiatives in bolstering company image, offering valuable insights for organizational stakeholders.